Filipino University Students’ Attitude Toward Sexual Minorities: Implications for International Students in Transition - Adeyemo, Kolawole Samuel (Journal of International Students, 2020)
Whether or not sexual minorities in the Philippines higher education system are socially acceptable is not clear. This article specifically investigates the acceptance of gay and lesbian university students in the Philippines and implications for international gay or lesbian students’ sociocultural transition. We sampled opinions of both local and international students in all the academic departments of a private university in the province of Cavite. The participants were selected using a proportionate stratified convenience sampling technique according to which they were grouped by academic department and chosen based on their availability, proximity, and convenience. We administered surveys to 368 registered students in 2011. Of the 368 questionnaires distributed, 358 responses were received, which constitutes a 97.3% response rate. Using transition theory, the article argues that the attitude toward sexual orientation had some negative implications for gay and lesbian international students transitioning into the sociocultural environment of the Philippines.